A modified energy-saving skyhook for active suspension based on a hybrid electromagnetic actuator. (January 2019) - Ding, Renkai; Wang, Ruochen; Meng, Xiangpeng; Chen, Long
This study proposes a modified energy-saving skyhook consisting of active control, energy regeneration, and switch. The modified skyhook coordinates the contradiction between dynamic performance and energy consumption of electromagnetic active suspension. The control principle is analyzed, the switch condition between active control and energy recovery is provided, and the switch control system is designed for simulation. Results demonstrate that the presented strategy can coordinate the dynamic performance and energy consumption effectively. The realization structure, namely, a hybrid electromagnetic actuator, is then designed to satisfy the control requirements. It integrates a linear motor and a hydraulic damper. The linear motor is used for active control or energy regeneration, while the hydraulic damper is used to guarantee basic dynamic performance. The structural dimension of hybrid electromagnetic actuator is optimized to increase air gap flux density with the volume and weight limitation. A prototype is fabricated, and a bench test is conducted. Results show that the structure can satisfy the control requirements. Some errors within a reasonable range are also observed between the test and the simulation because the simulation model is prepared under ideal conditions.